Curtsies & conspiracies - Carriger, Gail (Carriger, Gail. Finishing school, 2014)
Sophronia is excelling at her second year at Mademoiselle Geraldine's Finishing Academy for Young Ladies of Quality. Training in espionage, she uses her newly acquired skills to learn the true reason behind the school trip to London, one that includes boys. What she uncovers is a whirl-wind London season, full dance cards, and conspiracy involving a technology that will affect vampires, werewolves, and humans alike.